Phillyrin Attenuates Osteoclast Formation and Function and Prevents LPS-Induced Osteolysis in Mice - Wang, Jing; Chen, Gang; Zhang, Qianqian; Zhao, Fuli; Yu, Xiaolu; Ma, Xuemei; Liu, Mei (Frontiers in Pharmacology, 2019)
As the sole cell type responsible for bone resorption, osteoclasts play a pivotal role in a variety of lytic bone diseases. Suppression of osteoclast formation and activation has been proposed as an effective protective therapy for new bone. In this study, we reported for the first time that phillyrin (Phil), an active ingredient extracted from forsythia, significantly inhibited RANKL-induced osteoclastogenesis and bone resorption in vitro and protected against lipopolysaccharide-induced osteolysis in vivo. Further molecular investigations demonstrated that Phil effectively blocked RANKL-induced activations of c-Jun N-terminal kinase and extracellular signal-regulated kinase, which suppressed the expression of c-Fos and nuclear factor of activated T-cells cytoplasmic 1. Taken together, these data suggested that Phil might be a potential antiosteoclastogenesis agent for treating osteoclast-related bone lytic diseases.